Accurate atomic displacement parameters from time‐of‐flight neutron‐diffraction data at TOPAZ. Issue 6 (19th September 2014) - Jørgensen, Mads R. V.; Hathwar, Venkatesha R.; Sist, Mattia; Wang, Xiaoping; Hoffmann, Christina M.; Briseno, Alejandro L.; Overgaard, Jacob; Iversen, Bo B.
<x xml:space="preserve">Abstract</x> Accurate atomic displacement parameters (ADPs) are a good indication of high‐quality diffraction data. Results from the newly commissioned time‐of‐flight Laue diffractometer TOPAZ at the SNS are presented. Excellent agreement is found between ADPs derived independently from the neutron and X‐ray data emphasizing the high quality of the data from the time‐of‐flight Laue diffractometer.